Der indirekten Translation auf der Spur – „Koelie“ von Madelon Székely-Lulofs in polnischer Übersetzung - Michał Gąska (Studia Translatorica, 2020)
The present article deals with the indirect translation, which is conceived by many translation theoreticians as an inadvisable practice. The aim of the paper is to prove that the Polish rendering of the novel “Koelie” by the Dutch writer Madelon Székely-Lulofs is in fact an indirect translation. The case study draws on a triangulation method consisting of peritextual, epitextual and comparative analysis. The epitextual analysis enabled to advance a hypothesis, that the translator of the novel into Polish – Herminia Bukowska – might have rendered indirect either via the German or English version. On the basis of the comparative analysis of the source text with its renderings into German, English and Polish carried out with regard to the so-called third culture elements, was it possible to verify this hypothesis. The comparison revealed quite a few unambiguous similarities between the Polish and German rendering in the translators’ approach in relation to the mentioned translation units, which in turn differ from the source text.